PREDIKSI LAJU EROSI DENGAN METODE UNIVERSAL SOIL LOSS EQUATION (USLE) DI KECAMATAN BANAWA SELATAN - Halim, Suhasrianto S; Monde, Anthon; Hasanah, Uswah (AGROTEKBIS, 2019)
Study has been conducted to determine erosion hazard occurring in South Banawa District. This research was conducted in September - November 2017. This study conducted by field observations and was supported by results of laboratory analysis data. The rate of erosion was determinad by using the USLE (Universal Soil Loss Equation) method developed by Wischmeier and Smith in 1965. The results showed that the erosion hazard occurring in South Banawa Sub-District is very high with the average erosion per year reaches 1,785 ton ha-1 year-1 (medium). Conservation practices are required for reducing the rate of erosion hazard by the estaldishmeat of terraces, contour planting and replanting at lands with a slope above 15%.